Acting do personagem em animação e o processo de produção - Andrade, Maurício Vidal Silva de (2017)
The present study aims to investigate the use of acting techniques, from the performing arts, in the creation of animated scenes in productions for cinema, television or new media. After the rise of Animation’s 2nd Golgen Age, in the mid-1990s, with the release of ‘Toy Story’ movie, the digital animation technique came to gain space in movies productions and visual effects. The development of the use of this technique occurred as the internet was established as a media for the whole society. Through online videos and trainings, as well as animated movie extras, there is a growing discussion and use of acting techniques as part of the production process for animation, even though the principles of traditional animation remain behind the success of digital animation movies. The qualitative methodology used was the Content Analysis technique, following the model of Laurence Bardin (1988) that allows the inference of knowledge about the sender or the recipient of the communication. The corpus of the research was composed by experienced and award-winning Brazilian animators. We propose an overview of the animation production process to more clearly illustrate the issues related to the insertion of acting in animation and the reflections that can be generated